2018
DOI: 10.1111/jth.13894
|View full text |Cite|
|
Sign up to set email alerts
|

Rivaroxaban reversal with prothrombin complex concentrate or tranexamic acid in healthy volunteers

Abstract: Essentials• Specific reversal agents for managing severe factor Xa inhibitor-associated bleeding are lacking.• We assessed 4-factor-prothrombin complex concentrate (4F-PCC) and tranexamic acid (TXA).• 4F-PCC, but not TXA, reduced the prothrombin time and increased endogenous thrombin potential.• These agents may be viable options for reversal of therapeutic doses of rivaroxaban.Summary. Background: Oral activated factor X inhibitors such as rivaroxaban are widely used, but specific reversal agents are lacking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 16 publications
0
43
0
Order By: Relevance
“…4FPCC (50 IU/kg) reduced bleeding duration after punch biopsy in edoxaban‐treated human volunteer subjects . However, administration of 4FPCC or TXA to healthy volunteers on rivaroxaban had no effect on bleeding duration or bleeding volume following skin punch biopsy …”
Section: Pcc Apcc and Recombinant Factor Viia For Reversal Of Factormentioning
confidence: 99%
See 2 more Smart Citations
“…4FPCC (50 IU/kg) reduced bleeding duration after punch biopsy in edoxaban‐treated human volunteer subjects . However, administration of 4FPCC or TXA to healthy volunteers on rivaroxaban had no effect on bleeding duration or bleeding volume following skin punch biopsy …”
Section: Pcc Apcc and Recombinant Factor Viia For Reversal Of Factormentioning
confidence: 99%
“…A total of 8 animal studies, 13 in vitro human volunteer studies, and 8 in vivo human volunteer studies evaluated the use of PCC, aPCC, or rFVIIa to reverse the anticoagulant effect of direct factor Xa inhibitors (Tables ).…”
Section: Pcc Apcc and Recombinant Factor Viia For Reversal Of Factormentioning
confidence: 99%
See 1 more Smart Citation
“…[56][57][58] Testing may be considered after careful counselling in younger patients with an unprovoked VTE and a strong family history, particularly if cessation of anticoagulation is being considered. 64 As such, other options should be considered including drug discontinuation, supportive care and use of other haemostatic agents. Andexanet alfa (andexanet) and ciraparantag are two agents in advanced clinical trials.…”
Section: Thromobophilia Testingmentioning
confidence: 99%
“…A recent study reported that four-factor prothrombin complex concentrate partially reverses the anticoagulant effect of rivaroxaban but has no significant effect on bleeding duration, and tranexamic acid does not have any measurable effects. 64 As such, other options should be considered including drug discontinuation, supportive care and use of other haemostatic agents. For further management strategies with regards to management of DOAC-related bleeding, we refer to the previously published IMJ article.…”
Section: Thromobophilia Testingmentioning
confidence: 99%